Combining brine or CO2 geothermal preheating with low-temperature waste heat: A higher-efficiency hybrid geothermal power system. Issue 42 (December 2020) - Garapati, Nagasree; Adams, Benjamin M.; Fleming, Mark R.; Kuehn, Thomas H.; Saar, Martin O.
Highlights: A direct CO2 (CPG) hybrid geothermal cycle is compared with an indirect brine cycle. The hybrid power is compared to the combined power of individual systems. The hybrid cycle generates more power than individual cycles. An optimum auxiliary heat temperature is found to maximize hybrid generation. Direct CPG cycles can utilize lower temperature waste heat than indirect brine cycles. Abstract: Hybrid geothermal power plants operate by using geothermal fluid to preheat the working fluid of a higher-temperature power cycle for electricity generation. This has been shown to yield higher electricity generation than the combination of a stand-alone geothermal power plant and the higher-temperature power cycle. Here, we test both a direct CO2 hybrid geothermal system and an indirect brine hybrid geothermal system. The direct CO2 hybrid geothermal system is a CO2 Plume Geothermal (CPG) system, which uses CO2 as the subsurface working fluid, but with auxiliary heat addition to the geologically produced CO2 at the surface. The indirect brine geothermal system uses the hot geologically produced brine to preheat the secondary working fluid (CO2 ) within a secondary power cycle. We find that the direct CPG-hybrid system and the indirect brine-hybrid system both can generate 20 % more electric power than the summed power of individual geothermal and auxiliary systems in some cases. Each hybrid system has an optimum turbine inlet temperature which maximizes the electric power generated, and is typically between 100 °C and 200 °C in the systems examined. The optimum turbine inlet temperature tends to occur where the geothermal heat contribution is between 50 % and 70 % of the total heat addition to the hybrid system. Lastly, the CO2 direct system has lower wellhead temperatures than indirect brine and therefore can utilize lower temperature resources.